2000
DOI: 10.3171/jns.2000.92.4.0706
|View full text |Cite
|
Sign up to set email alerts
|

Intraparenchymal meningioma originating from underlying meningioangiomatosis

Abstract: The authors present the case of a 20-year-old woman with right-sided temporal intraparenchymal meningioma originating from underlying meningioangiomatosis. The patient manifested temporal-type seizures as the initial symptom. She had no stigmata of neurofibromatosis Type 2. Neuroradiological studies revealed an intraaxial, contrast-enhancing lesion in the right temporal lobe. After gross-total removal of the tumor, histological examination revealed a transitional meningioma with surrounding neural parenchyma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 15 publications
2
34
0
3
Order By: Relevance
“…This finding suggests that hormones may play an important role in the pathogenesis of MA-M. Wiebe et al suggested that the temporal lobe was the most frequently involved in MA [1], while the frontal lobe seemed to be more affected, based on our analysis. Rarely, MA has been documented to occur in the diencephalon [25], in the brain stem [43] and outside the cerebral cortex [54]. In our series, we reported an MA-M lesion (case 3) that was believed to be the first reported MA-M case involving the corpus callosum (Fig.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This finding suggests that hormones may play an important role in the pathogenesis of MA-M. Wiebe et al suggested that the temporal lobe was the most frequently involved in MA [1], while the frontal lobe seemed to be more affected, based on our analysis. Rarely, MA has been documented to occur in the diencephalon [25], in the brain stem [43] and outside the cerebral cortex [54]. In our series, we reported an MA-M lesion (case 3) that was believed to be the first reported MA-M case involving the corpus callosum (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Takeshima et al demonstrated that only 25 % of MA cases were associated with NF2, while in the remaining 75 %, it occurred sporadically [72]. Occasionally, MA has been reported to coexist with meningiomas [11,39,54,82], arteriovenous malformations [23], encephaloceles [75], oligodendrogliomas [50], meningeal hemangiopericytomas [39] and focal cortical dysplasia [65]. Among these, MA with meningioma is the most frequent combination.…”
Section: Discussionmentioning
confidence: 97%
“…En caso de ausencia de atipia celular, el patrón de crecimiento perivascular y la presencia de ovillos neurofibrilares en las neuronas del tejido cortical residual 10,22 apoyarían el diagnóstico de MA. También se ha descrito un caso de meningioma intraparenquimatoso bien delimitado del parénquima adyacente y constituido por células que expresaban vimentina y EMA, asociado a MA adyacente con ovillos neurofibrilares en el tejido cortical respetado 23 . Se postuló que el meningioma se originaba a partir de la MA, aunque también podría corresponder a un nódulo hiperplásico de la MA.…”
Section: Figura 2 Caso 2: En 2 a Se Aprecia Engrosamiento De La Lepunclassified
“…Meningioma associated with MA, is the most frequent combination and a rare condition mimicking invasive meningioma both pathologically and radiologically 15,29 . The most important differential diagnosis of meningioma with MA is because the prognosis and evolution of these 2 entities is entirely different 24 .…”
Section: Differential Diagnosismentioning
confidence: 99%